Bacterial Lipopolysaccharide Augmented Malignant Transformation and Promoted the Stemness in Prostate Cancer Epithelial Cells - Tang S; Lian X; Cheng H; Guo J; Ni D; Huang C; Gu X; Meng H; Jiang J; Li X (Dove Medical Press, 2021)
Sijie Tang,1,2 Xueqi Lian,1 Huiying Cheng,1 Jiaqian Guo,1 Daguang Ni,1 Can Huang,1 Xiang Gu,2 Hong Meng,3 Jiajia Jiang,1 Xiaohua Li1,4,5 1The Aoyang Cancer Institute, Affiliated Aoyang Hospital of Jiangsu University, Zhangjiagang, Suzhou, 215600, People's Republic of China; 2Department of Urology, the Affiliated Aoyang Hospital of Jiangsu University, Zhangjiagang, Suzhou, 215600, People's Republic of China; 3Perinatology Research Branch, Eunice Kennedy Shriver National Institute of Child Health and Human Development, National Institutes of Health, Detroit, MI, 48201, USA; 4The Laboratory of Clinical Genomics, Hefei KingMed Diagnostics Ltd, Hefei, 230088, People's Republic of China; 5National Center for Gene Testing Technology Application & Demonstration (Anhui), Hefei, 230088, People's Republic of ChinaCorrespondence: Xiaohua Li; Jiajia JiangThe Aoyang Cancer Institute, Affiliated Aoyang Hospital of Jiangsu University, 279 Jingang Blvd., Zhangjiagang, Suzhou, 215600, People's Republic of ChinaEmail joshua28li@163.com; 2111913004@stmail.ujs.edu.cnPurpose: To study bacterial lipopolysaccharide (LPS)-induced cancer stem-like transformation and to investigate the inhibitory effect of Trichostatin A (TSA) on the malignant transformation through targeting p-Stat3 signaling.Methods: 2D, 3D, and serum-free suspension culture system were used to study LPS-induced malignant transformation in series malignant grade of prostate cancer (PCa) epithelial cells. Flow cytometry assay and RT-PCR were utilized to evaluate the CD44+CD133+ stem cell population, the expression of inflammatory cytokines and series tumor stemness biomarkers. Meanwhile, Western blot was used to analyze the alteration of cell signaling associated-molecules by treatment with TSA, an original antifungal antibiotic and a panel inhibitor of histone deacetylase.Results: Our study found that LPS promoted the migration, invasion and stem-like tumoroshpere forming in multiple PCa cell lines including DU145, PC3, 22RV1, LNCaP. LPS also enriched CD44+CD133+ stem cell population and increased the expression of series tumor stemness biomarkers (e.g., CD44, CD133, SOX-2, α-intergrin, Nestin, etc.). TSA was found to prevent tumor cell migration, invasion and tumorosphere forming in DU145 and PC3 cells with increasing tumor suppressive Maspin and reducing both phosphorylation of Stat3 (p-Stat3) and pro-oncogene c-Myc expression in LPS-treated DU145 cells. Furthermore, blocking Stat3 signaling pathway by treatment with TSA and/or small molecule compound Stattic of an p-Stat3 inhibitor effectively abrogated LPS-induced tumorosphere forming with decrease of IL-6, IL-8 and stemness biomarkers CD44, SOX-2 expression.Conclusion: Our data demonstrated that the inflammatory agent of bacterial LPS augmented malignant transformation and promoted the cancerous stemness in PCa epithelial cells. TSA could prevent, at least in part, the LPS-induced malignant transformation by targeting p-Stat3/c-Myc signaling pathway and reducing inflammatory IL-6, IL-8. In addition, the assay of LPS-induced tumorosphere forming could serve as a simple and an easy handling method for targeting cancer stem cells drug screening in vitro in clinical practice.Keywords: tumorosphere forming, prostate cancer, bacterial lipopolysaccharide, epithelial malignant transformation, cancer stemness